The functional resonance analysis method as a health care research methodology: a scoping review protocol. Issue 3 (13th March 2021) - McGill, Alexis; Smith, Doug; McCloskey, Rose; Morris, Patricia; Goudreau, Alex; Veitch, Brian
ABSTRACT: Objective: The objective of this review is to examine and map the literature on the use of the functional resonance analysis method in health care research. Introduction: Health care systems are highly complex and involve interrelated functions, organizations, individuals, and technologies. Understanding how these elements interact and impact health care processes is difficult because of inherent contextual and human variables. The functional resonance analysis method offers an approach to deconstruct complex systems and examine relationships between individual processes and elements. By using the functional resonance analysis method, researchers can map health care processes and uncover performance variables that can emerge and strengthen, or compromise, intended outcomes. Insight into how the functional resonance analysis method has been operationalized in health care research will help researchers and policy makers understand how the method can be used to strengthen health care systems. Inclusion criteria: The scoping review will consider research and narrative reports on the application of the functional resonance analysis method in health care research. The concepts of interest are the research questions/aims/objectives, methods used to operationalize the functional resonance analysis method, key concepts and definitions of the functional resonance analysis method, and key findings. Studies that used the functional resonance analysis method in any health care setting will be considered. Methods: The scoping review will aim to locate published and unpublished literature by employing a three-step search strategy. Only papers published in English will be considered and no limits will be placed on the year of publication. Data extracted will include key concepts and definitions of the functional resonance analysis method, research questions/aims/objectives, methods used to operationalize the functional resonance analysis method, and key findings. Extracted data will be reported in tabular form and presented narratively to express the review question.